Adipose Tissue Inflammation Induces B Cell Inflammation and Decreases B Cell Function in Aging - Frasca, Daniela; Blomberg, Bonnie B. (Frontiers in Immunology, 2017)
Aging is the greatest risk factor for developing chronic diseases. Inflamm-aging, the age-related increase in low-grade chronic inflammation, may be a common link in age-related diseases. This review summarizes recent published data on potential cellular and molecular mechanisms of the age-related increase in inflammation, and how these contribute to decreased humoral immune responses in aged mice and humans. Briefly, we cover how aging and related inflammation decrease antibody responses in mice and humans, and how obesity contributes to the mechanisms for aging through increased inflammation. We also report data in the literature showing adipose tissue infiltration with immune cells and how these cells are recruited and contribute to local and systemic inflammation. We show that several types of immune cells infiltrate the adipose tissue and these include macrophages, neutrophils, NK cells, innate lymphoid cells (ILCs), eosinophils, T cells, B1 and B2 cells. Our main focus is how the adipose tissue affects immune responses, in particular B cell responses and antibody production. The role of leptin in generating inflammation and decreased B cell responses is also discussed. We report data published by us and by other groups showing that the adipose tissue generates pro-inflammatory B cell subsets which induce pro-inflammatory T cells, promote insulin resistance and secrete pathogenic autoimmune antibodies.